Experiments on the Performance of Small Horizontal Axis Wind Turbine with Passive Pitch Control by Disk Pulley - Yu-Jen Chen; Y. C. Shiah (Energies, 2016)
The present work is to design a passive pitch-control mechanism for small horizontal axis wind turbine (HAWT) to generate stable power at high wind speeds. The mechanism uses a disk pulley as an actuator to passively adjust the pitch angle of blades by centrifugal force. For this design, aerodynamic braking is caused by the adjustment of pitch angles at high wind speeds. As a marked advantage, this does not require mechanical brakes that would incur electrical burn-out and structural failure under high speed rotation. This can ensure the survival of blades and generator in sever operation environments. In this paper, the analysis uses blade element momentum theory (BEMT) to develop graphical user interface software to facilitate the performance assessment of the small-scale HAWT using passive pitch control (PPC). For verification, the HAWT system was tested in a full-scale wind tunnel for its aerodynamic performance. At low wind speeds, this system performed the same as usual, yet at high wind speeds, the equipped PPC system can effectively reduce the rotational speed to generate stable power.